Comprehensive Description of Biosimilars Regulatory Framework in Brazil - Kethareshwara Sujatha Deeksha; Balamuralidhara Veeranna (Pharmaceutical Research: Recent Advances and Trends Vol. 6, 2024)
Biological products, also known as biopharmaceuticals, are medications derived from biological systems and then created utilizing contemporary biotechnological techniques. These biological products are very different from traditional synthetic drugs in several important respects. They are much larger and more complex molecules with inherent diversity therefore, different manufacturers cannot produce identical biological products, even with the same type of host expression system and equivalent technologies. Thus, legal follow-on biologics manufactured and marketed after patent expiration are usually referred to as biosimilars. Brazil is the ninth-largest economy in the world, and it boasts one of the biggest and most complicated healthcare systems in the region. The Brazilian Health Regulatory Agency (ANVISA) plays a pivotal role in shaping the biosimilar landscape, balancing innovation with safety, efficacy, and accessibility. Biosimilars are required to satisfy various regulatory requirements before being permitted to enter the market in various regions. Other issues that are related to this need to be established by national authorities. These issues include interchangeability, labeling, and prescription information. The Brazilian health monitoring agency follows the fundamental criteria established by the World Health Organization for evaluating bio-similarity; nevertheless, it does not make use of the name "biosimilar." The objective of this article is to present the Brazilian biosimilar law.